Modified heterocyclic aramid fiber and preparation method thereof
By adding the graphene oxide dispersion liquid to the aramid III monomer polymerization reaction system, a composite spinning liquid is formed and modified heterocyclic aramid fibers are prepared through wet spinning technology, which solves the problems of poor mechanical properties of domestic fibers and degraded mechanical properties of graphene oxide, and achieves high mechanical properties and long-term stability of the fibers.
Patent Information
- Application Number
- CN202311278124.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2043-09-28
AI Technical Summary
There is a big gap between the mechanical properties of domestically produced heterocyclic aramid fibers and foreign countries, and the mechanical properties of graphene oxide will slowly decline during storage and use after being added to the fibers.
A dispersion liquid formed by dispersing graphene oxide in N,N-dimethylacetamide solvent was added to the aramid III monomer polymerization system to form a composite spinning liquid, and modified heterocyclic aramid fibers were prepared by wet spinning technology. The temperature of the thermal stretching step was 400-420℃.
The mechanical properties and long-term stability of the fiber are improved, fibrillation is prevented, compression properties, tensile strength and corrosion resistance are enhanced, and graphene oxide is easier to partially reduce during fiber forming, and the performance of the obtained fiber remains stable during storage and use.
Smart Images

Figure CN119710963A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of heterocyclic aramid fibers, and more specifically to graphene oxide-modified heterocyclic aramid fibers and a preparation method thereof. Background Art
[0002] Heteroaramid fiber is an organic high-performance fiber with excellent properties such as light weight, high strength, high modulus, and impact resistance. It has important applications in aerospace and defense industries such as engine casings of weapon systems, bulletproof helmets, and aircraft skins. In engineering applications, domestic heteroaramid fibers still face a large gap in mechanical properties compared to foreign ones, and their use areas are relatively limited. Therefore, how to develop a series of fiber products based on the structural weaknesses of heteroaramid fibers and the needs of actual application scenarios is the key to realizing the application of heteroaramid fibers. Graphene is composed of sp 2 Two-dimensional nanocarbon materials composed of hybrid carbon atoms arranged in a honeycomb-like structure have the characteristics of high strength, high modulus and high specific surface area, and are ideal structural reinforcement materials.
[0003] At present, some studies have introduced graphene into heterocyclic aramid fibers. For example, in Chinese invention patent CN113718364A, graphene materials are added to aramid polymer solution as graphene aramid spinning solution. However, direct mixing easily causes graphene agglomeration, making the aramid composite fibers obtained by spinning uneven, with poor stability and mechanical properties, making them difficult to use in actual production.
[0004] Compared with the above-mentioned method of directly adding graphene powder, pre-configuring a graphene dispersion can improve the dispersibility of graphene in the spinning solution to a certain extent, such as dissolving graphene (graphene oxide or amino graphene with carboxyl group) in N, N dimethylacetamide / lithium chloride composite solvent in Chinese invention patent CN115216857A to obtain a dispersion of graphene, and then adding aramid monomers p-phenylenediamine, 2-(4-aminophenyl)-5-aminobenzimidazole, and terephthaloyl chloride to the graphene dispersion to obtain graphene aramid spinning solution. However, lithium chloride in the composite solvent is prone to cause the agglomeration of graphene due to the salt ion effect, so the graphene dispersion cannot be stored for a long time, and is only applicable to the preparation of spinning solution immediately after the preparation is completed, which brings many inconveniences to actual production. In addition, dissolving p-phenylenediamine and 2-(4-aminophenyl)-5-aminobenzimidazole in the dispersion of graphene oxide will also have an adverse effect on the dispersibility of graphene.
[0005] In order to ensure the better application of aramid fiber, its stability has become an important evaluation standard. At present, many studies have achieved the enhancement effect by introducing graphene oxide into the aramid system. For example, in the Chinese invention patent CN115216857A, graphene oxide with carboxyl groups is added to the aramid system. However, the addition of graphene oxide will cause the mechanical properties of the composite fiber to slowly decrease during the later storage and use process, which brings huge hidden dangers to the application of the fiber. Summary of the invention
[0006] In order to improve the long-term stability of the mechanical properties of the fiber, the present invention provides a method for preparing a modified heterocyclic aramid fiber and the modified heterocyclic aramid fiber prepared by the method.
[0007] The invention discloses a method for preparing a modified heterocyclic aramid fiber, comprising: S1, dispersing graphene oxide in an N,N-dimethylacetamide solvent to form a dispersion; S2, adding the dispersion into a polymerization reaction system before polymerization of aramid III monomer to form a composite spinning solution; and S3, using wet spinning to form the modified heterocyclic aramid fiber from the composite spinning solution, wherein the temperature of the hot stretching step is 400-420°C; wherein CO / C=O in the graphene oxide is 2-5.
[0008] According to one embodiment of the present invention, the carbon-oxygen ratio of the graphene oxide is 2-5, the number of layers is 1-10, and the sheet diameter is 0.01-3 μm; preferably, the number of layers is 1-3.
[0009] According to another embodiment of the present invention, the mass percentage of the graphene oxide in the dispersion is 0.05-0.5%.
[0010] According to another embodiment of the present invention, the S2 step comprises: dissolving lithium chloride cosolvent, p-phenylenediamine and 2-(4-aminophenyl)-5-aminobenzimidazole in N,N-dimethylacetamide solvent to form a solution, reducing the solution temperature to -10-10°C and then adding the dispersion, stirring for 5-20 minutes, and then adding terephthaloyl chloride to react to obtain the composite spinning solution.
[0011] According to another embodiment of the present invention, the viscosity of the composite spinning solution is 30,000-100,000 centipoise.
[0012] According to another embodiment of the present invention, the mass percentage of the graphene oxide in the modified heterocyclic aramid fiber is 0.02-0.8%.
[0013] The present invention also provides a modified heterocyclic aramid fiber prepared by the method.
[0014] The present invention uses graphene oxide with high CO content and a dispersion formed with N,N-dimethylacetamide as a solvent. Since graphene oxide is not easy to agglomerate in a composite solvent and is easy to store, CO in graphene oxide is more likely to be partially reduced during the fiber forming process to obtain reduced graphene oxide, which is more stable than graphene oxide and ensures the subsequent stable storage of fibers. At the same time, the addition of graphene oxide in the present invention can also prevent fiber fibrillation, greatly improving compression performance, tensile strength and corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 It is a schematic diagram and a physical picture of the reduced graphene oxide modified heterocyclic aramid fiber during the fiber forming process of one embodiment of the present invention.
[0016] Figure 2 These are the XPS spectra and thermogravimetric images of graphene oxide before and after heat treatment.
[0017] Figure 3 are photographs of the storage process of the dispersions of Example 1 and Comparative Example 1.
[0018] Figure 4 These are photos of the modified heterocyclic aramid prepared in Example 1 and Comparative Example 1 in the organic solvent DMAc. DETAILED DESCRIPTION
[0019] Typical embodiments that embody the features and advantages of the present invention will be described in detail in the following description. It should be understood that the present invention can have various changes in different embodiments without departing from the scope of the present invention, and the descriptions and drawings therein are essentially used for illustration rather than for limiting the present invention.
[0020] The preparation method of the modified heterocyclic aramid fiber of the present invention comprises: S1, dispersing graphene oxide in N,N-dimethylacetamide solvent to form a dispersion; S2, adding the dispersion into a polymerization reaction system before the polymerization of aramid III monomer to form a composite spinning solution; and S3, using wet spinning to form the modified heterocyclic aramid fiber from the composite spinning solution, wherein the temperature of the hot stretching step is 400-420°C; wherein CO / C=O in the graphene oxide is 2-5.
[0021] In the present invention, "CO" refers to a CO bond; "C=O" refers to a C=O bond. The CO bond may be C-OH and / or COC. "CO / C=O" refers to the molar ratio or mass ratio of the CO bond to the C=O bond.
[0022] The present invention uses graphene oxide and a dispersion formed with N,N-dimethylacetamide as a solvent. Since graphene oxide is not easy to agglomerate in a composite solvent and is easy to store, and does not require any dispersant (such as lithium chloride or calcium chloride) to form a dispersion with good dispersibility, and no impurities are introduced into the system without other additives, the stability of subsequent reactions can be guaranteed. The present invention selects graphene oxide with more CO (CO / C=O is 2-5), and compared with the C=O bond, the CO bond energy is lower, and it is easier to be partially reduced during the fiber forming process to obtain reduced graphene oxide, which is more stable than graphene oxide, and ensures the subsequent stable storage of fibers.
[0023] Figure 1 The XPS spectra and thermogravimetric diagrams of graphene oxide before and after heat treatment are shown. Figure a is the XPS spectrum of graphene oxide, from which it can be seen that graphene oxide contains more functional groups. Figure b is the XPS spectrum of graphene oxide after treatment at 400°C, from which it can be seen that some functional groups are reduced, and the functional groups containing CO bonds are reduced to a greater extent than those containing C=O bonds, which proves that CO bonds are easier to reduce than C=O bonds. Figure c is a thermogravimetric curve, and the thermogravimetric results show that at around 200°C, most of the functional groups of graphene oxide disappear, the weight drops sharply, and then almost maintains equilibrium. Figure 1 The information shown can prove that graphene oxide has more CO bonds and is easier to be reduced.
[0024] Figure 2 The following is a schematic diagram and a physical picture (far right) of a graphene oxide modified heterocyclic aramid fiber reduced during the fiber forming process according to an embodiment of the present invention. The modified heterocyclic fiber prepared by the method of the present invention is green in color. The ordinary graphene oxide composite fiber is brown. Figure 1 It can be inferred that the preparation method of the present invention uses graphene oxide with a high CO content, so the graphene oxide is more easily reduced during the stretching process, resulting in a change in the color of the prepared fiber.
[0025] Furthermore, the addition of graphene oxide in the present invention can also prevent fiber fibrillation and greatly improve the compression performance.
[0026] Therefore, the method of the present invention takes into account the dispersibility of graphene oxide and improves the mechanical properties and long-term stability of the composite fiber.
[0027] In an optional embodiment, the carbon-oxygen ratio of graphene oxide is 2-5, the number of layers is 1-10 layers, and the sheet diameter is 0.01-3μm. Preferably, the number of layers is 1-3 layers. The carbon-oxygen ratio of graphene oxide is between 2-5 to ensure the uniform dispersion of graphene oxide in DMAc, and it is easily reduced by heat treatment. The carbon-oxygen ratio is too low (lower than 2), the oxygen content of graphene oxide is too high and there are many defects, which is not conducive to the improvement of mechanical properties; the carbon-oxygen ratio is too high (higher than 5) is not conducive to the dispersion of graphene oxide. The sheet diameter of graphene oxide is between 0.01-3μm and is selected according to its dispersibility and the diameter of the fiber. Generally, the fiber diameter is 10μm. If the sheet diameter is too large (greater than 3μm), it will cause spinning plugging and mechanical properties will decrease; the sheet diameter is selected in this range, and the graphene oxide has good dispersibility in the dispersion liquid and high spinnability.
[0028] In an optional embodiment, the mass percentage of graphene oxide in the dispersion is 0.05-0.5%.
[0029] In an optional embodiment, step S2 includes: dissolving lithium chloride cosolvent, p-phenylenediamine and 2-(4-aminophenyl)-5-aminobenzimidazole in N,N-dimethylacetamide solvent to form a solution, adding the dispersion after lowering the solution temperature to -10-10°C, stirring for 5-20 minutes, and then adding terephthaloyl chloride to react to obtain a composite spinning solution. Wherein lithium chloride cosolvent, p-phenylenediamine and 2-(4-aminophenyl)-5-aminobenzimidazole are added to N,N-dimethylacetamide solvent, and can be stirred under nitrogen protection until completely dissolved, and the stirring time can be 5-20 minutes. After the temperature of the solution is lowered, terephthaloyl chloride can be added in batches and stirred sufficiently to cause a polymerization reaction to obtain a composite spinning solution.
[0030] In the present invention, in the polymerization process (step S2), the graphene oxide dispersion is added to a solution in which 2-(4-aminophenyl)-5-aminobenzimidazole and p-phenylenediamine are completely dissolved in advance, and terephthaloyl chloride is added in batches after stirring for 5-20 minutes. The advantages are as follows: firstly, 2-(4-aminophenyl)-5-aminobenzimidazole and p-phenylenediamine are mixed with the graphene oxide dispersion in the form of a mixed solvent, which can effectively avoid the agglomeration of graphene oxide caused by solid-state, high-adhesion 2-(4-aminophenyl)-5-aminobenzimidazole and p-phenylenediamine, and at the same time, adding the graphene oxide dispersion into the pre-dissolved 2-(4-aminophenyl)-5-aminobenzimidazole and p-phenylenediamine / N,N-dimethylacetamide solution can reduce the stirring time of graphene oxide in the reactor, so that the graphene oxide can be well dispersed in the composite solvent without agglomeration; secondly, the graphene oxide is added before terephthaloyl chloride to participate in the polymerization process of the aramid monomer, so that the graphene oxide can be well dispersed in the polymer without agglomeration, thereby improving the mechanical properties of the fiber.
[0031] In an optional embodiment, the viscosity of the composite spinning solution is 30,000-100,000 centipoise.
[0032] In an optional embodiment, the preparation method further includes: S3, forming a modified heterocyclic aramid fiber from the composite spinning solution by wet spinning. The wet spinning process can be, but is not limited to, vacuum degassing the composite spinning solution, and then evenly spraying it from the spinneret, through a primary coagulation bath for double diffusion and a certain stretching effect to form a primary fiber, and then through a secondary coagulation bath, washing, drying, and then entering a temperature of 400-420°C and a nitrogen atmosphere for heat stretching treatment, at which time the graphene oxide inside the aramid can be partially reduced, and finally rolled into a partially reduced graphene oxide / heterocyclic aramid composite fiber.
[0033] In an optional embodiment, the mass percentage of graphene oxide in the modified heterocyclic aramid fiber is 0.02-0.8%. If the amount of graphene oxide added exceeds a certain limit, the dispersibility of graphene oxide in the composite polymer solution will decrease, which will lead to unbalanced mechanical properties of the composite fiber. The present invention controls the mass content of graphene oxide in the modified heterocyclic aramid fiber to 0.02-0.8% of the fiber matrix. The advantage of this addition is that it is conducive to the uniform dispersion of graphene oxide in the polymer.
[0034] The present invention also provides a modified heterocyclic aramid fiber prepared by the above method. The tensile properties, compressive properties and interface properties of the fiber of the present invention are improved. After being placed for a certain period of time, the mechanical properties of the fiber of the present invention remain stable, while the ordinary heterocyclic aramid fiber will show a decrease of -1 cN / dtex. In addition, the mechanical property stability of the fiber of the present invention in organic solvents such as DMSO, DMF, DMAc, etc. is also improved.
[0035] The present invention is further described below by specific examples. However, these examples are merely exemplary and do not constitute any limitation to the scope of the present invention. In the following examples and comparative examples, the reagents, materials and instruments used are all commercially available unless otherwise specified.
[0036] Example 1
[0037] Graphene oxide powder (CO / C=O is 3, carbon oxygen ratio is 2.8, 3 layers, and flake diameter is 300nm) with a polymer mass fraction of 0.02% was placed in a 100°C oven for drying for 8 hours. Then the graphene oxide powder was taken out and added to N,N-dimethylacetamide organic solvent for ultrasonic dispersion for 30-60 minutes to obtain a uniform and stable graphene oxide dispersion.
[0038] Add the cosolvent LiCl, p-phenylenediamine, and 2-(4-aminophenyl)-5-aminobenzimidazole polymerization monomer into a reactor containing N,N-dimethylacetamide, and stir under nitrogen until completely dissolved. Lower the temperature of the above solution to 10°C, add the above prepared graphene oxide dispersion into the above solution and stir. Stir for 20 minutes, add terephthaloyl chloride in batches, and stir for 5 hours to obtain a composite spinning solution.
[0039] The composite spinning solution is vacuum degassed and then uniformly ejected from the spinneret. It is then subjected to double diffusion and a certain stretching action in a primary coagulation bath to form primary fibers. It is then subjected to a secondary coagulation bath, washed with water, dried, and then subjected to heat stretching treatment at a temperature of 400°C in a nitrogen atmosphere. The graphene oxide inside the aramid can be partially reduced and finally rolled into partially reduced graphene oxide / heterocyclic aramid composite fibers. The color of the composite fibers is green. The tensile strength of the composite fibers was measured to be 35.74 cN / dtex. Three months later, the tensile strength of the composite fibers was measured to be 36.38 cN / dtex, and the performance remained stable.
[0040] Figure 3 The storage conditions of the graphene oxide dispersion prepared in this example and the dispersion with lithium chloride added (Comparative Example 1) are shown. It can be seen from the figure that the graphene oxide can be dispersed in N,N-dimethylacetamide and can be kept without agglomeration for up to 30 days. In contrast, the graphene oxide dispersed in the N,N-dimethylacetamide / lithium chloride composite solvent has obvious precipitation after one day.
[0041] Figure 4 The photos of heterocyclic aramid and the modified heterocyclic aramid fiber prepared in this example after 20 minutes in the organic solvent DMAc are shown. The heterocyclic aramid fiber is completely swollen after 20 minutes in the organic solvent DMAc, while the modified aramid fiber prepared in this example does not swell after 20 minutes in the organic solvent DMAc, and swells completely after one month. This proves that the modified heterocyclic aramid fiber prepared by the method of the present invention has good mechanical property stability in organic solvents.
[0042] Example 2
[0043] Except that the mass content of graphene oxide in the modified aramid fiber is 0.1%, other conditions are the same as those in Example 1.
[0044] The tensile strength of the modified heterocyclic aramid fiber prepared in this embodiment was measured to be 36.34 cN / dtex. Three months later, the tensile strength of the composite fiber was measured to be 36.68 cN / dtex, and the performance remained stable.
[0045] Example 3
[0046] Except that the mass content of graphene oxide in the modified aramid fiber is 0.2%, other conditions are the same as those in Example 1.
[0047] The tensile strength of the modified heterocyclic aramid fiber prepared in this embodiment was measured to be 37.22 cN / dtex. Three months later, the tensile strength of the composite fiber was measured to be 37.96 cN / dtex, and the performance remained stable.
[0048] Example 4
[0049] Except that the mass content of graphene oxide in the modified aramid fiber is 0.3%, other conditions are the same as those in Example 1.
[0050] The tensile strength of the modified heterocyclic aramid fiber prepared in this embodiment was measured to be 38.28 cN / dtex, and the tensile strength of the composite fiber was measured to be 38.68 cN / dtex three months later, and the performance was stable and unchanged.
[0051] Example 5
[0052] Except that the mass content of graphene oxide in the modified aramid fiber is 0.5%, other conditions are the same as those in Example 1.
[0053] The tensile strength of the modified heterocyclic aramid fiber prepared in this embodiment was measured to be 36.67 cN / dtex. The tensile strength of the composite fiber was measured to be 37.34 cN / dtex three months later, and the performance remained stable.
[0054] Example 6
[0055] Except that the mass content of graphene oxide in the modified aramid fiber is 0.8%, other conditions are the same as those in Example 1.
[0056] The tensile strength of the modified heterocyclic aramid fiber prepared in this embodiment was measured to be 35.38 cN / dtex. Three months later, the tensile strength of the composite fiber was measured to be 36.01 cN / dtex, and the performance remained stable.
[0057] Example 7
[0058] Except for the graphene oxide powder (CO / C=O is 2), other conditions are the same as those in Example 4.
[0059] The tensile strength of the modified heterocyclic aramid fiber prepared in this embodiment was measured to be 37.98 cN / dtex. Three months later, the tensile strength of the composite fiber was measured to be 38.52 cN / dtex, and the performance remained stable.
[0060] Example 8
[0061] Except for the graphene oxide powder (CO / C=O is 4), other conditions are the same as those in Example 4.
[0062] The tensile strength of the modified heterocyclic aramid fiber prepared in this embodiment was measured to be 38.78 cN / dtex. Three months later, the tensile strength of the composite fiber was measured to be 39.05 cN / dtex, and the performance remained stable.
[0063] Example 9
[0064] Except for the graphene oxide powder (CO / C=O is 5), other conditions are the same as those in Example 4.
[0065] The tensile strength of the modified heterocyclic aramid fiber prepared in this embodiment was measured to be 38.29 cN / dtex. Three months later, the tensile strength of the composite fiber was measured to be 38.94 cN / dtex, and the performance remained stable.
[0066] Comparative Example 1
[0067] Except that the dispersion liquid of graphene oxide powder adopts N,N'-dimethylacetamide / lithium chloride composite solvent, other conditions are the same as those in Example 4.
[0068] The tensile strength of the composite fiber was measured to be 32.33 cN / dtex. Figure 1 It can be seen that the dispersion of the comparative example obviously shows graphene agglomeration, which is the reason why the mechanical properties of the fiber are not as good as those of the above-mentioned embodiment.
[0069] Comparative Example 2
[0070] The graphene oxide dispersion was added to the dissolved terephthaloyl chloride solution, and then other diamine monomers were added. The other reaction conditions were the same as those in Example 4.
[0071] During the reaction, it was observed that graphene agglomeration was obviously observed in the polymer solution. The tensile strength of the modified fiber prepared in this comparative example was measured to be 29.83 cN / dtex.
[0072] Comparative Example 3
[0073] Without pre-dissolving p-phenylenediamine and 2-(4-aminophenyl)-5-aminobenzimidazole, the above-mentioned polymerizable monomers were directly added to the graphene oxide dispersion, and then terephthaloyl chloride was added. Other conditions were the same as those in Example 4.
[0074] During the reaction, it was observed that graphene agglomeration was obviously observed in the polymerization solution. The tensile strength of the modified fiber was measured to be 32.83 cN / dtex.
[0075] Comparative Example 4
[0076] Except that the CO / C=O of the graphene oxide is 0.9, other conditions are the same as those in Example 4.
[0077] By comparison, it can be seen that the color of the carboxylated graphene oxide heterocyclic aramid composite fiber is brown, and the tensile strength of the composite fiber is measured to be 35.11 cN / dtex. Three months later, the tensile strength is measured to be 33.21 cN / dtex, and the mechanical properties are unstable.
[0078] Comparative Example 5
[0079] Except that the mass content of graphene oxide in the modified aramid fiber is 2%, other conditions are the same as those in Example 4.
[0080] During the reaction, it was observed that graphene in the polymerization solution agglomerated in a large area. The tensile strength of the modified fiber was measured to be 28.97 cN / dtex.
[0081] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for preparing a modified heterocyclic aramid fiber, characterized in that: include: S1, dispersing graphene oxide in N,N-dimethylacetamide solvent to form a dispersion; S2, adding the dispersion into the polymerization reaction system before the polymerization of the aramid III monomer to form a composite spinning solution; S3, forming the modified heterocyclic aramid fiber from the composite spinning solution by wet spinning, wherein the temperature of the hot stretching step is 400-420° C.; Wherein, CO / C=O in the graphene oxide is 2-5.
2. The preparation method according to claim 1, characterized in that: The graphene oxide has a carbon-oxygen ratio of 2-5, a number of layers of 1-10, and a sheet diameter of 0.01-3 μm; preferably, the number of layers is 1-3.
3. The preparation method according to claim 1, characterized in that: The mass percentage of the graphene oxide in the dispersion is 0.05-0.5%.
4. The preparation method according to claim 1, characterized in that: The S2 step includes: Lithium chloride cosolvent, p-phenylenediamine and 2-(4-aminophenyl)-5-aminobenzimidazole are dissolved in N,N-dimethylacetamide solvent to form a solution, the solution temperature is lowered to -10-10°C, the dispersion is added, and after stirring for 5-20 minutes, terephthaloyl chloride is added to react to obtain the composite spinning solution.
5. The preparation method according to claim 4, characterized in that: The viscosity of the composite spinning solution is 30,000-100,000 centipoise.
6. The preparation method according to claim 1, characterized in that: The mass percentage of the graphene oxide in the modified heterocyclic aramid fiber is 0.02-0.8%.
7. A modified heterocyclic aramid fiber, characterized in that: Prepared by the preparation method according to any one of claims 1 to 6.
Citation Information
Patent Citations
Graphene high-strength impact-resistant aramid fiber and preparation method thereof
CN113718364A
Preparation method of graphene modified high-strength and high-modulus heterocyclic aramid
CN115216857A
Olefinic carbon material dispersion liquid and application thereof
CN113248739A
Ultralow-oxygen-content three-dimensional nitrogen-doped graphene aerogel and preparation method thereof
CN113387346A
Preparation method of high-performance graphene fiber and graphene fiber
CN114959948A
Cited By
Graphene oxide slurry, modified para-aramid fiber and conductive aramid fiber preparation method
CN120350549A